A genetic advance: lipoprotein(a) in aortic stenosis. (June 2013) - Yanagawa, Bobby; Gupta, Nandini; Verma, Subodh
Evaluation of: Thanassoulis G, Campbell CY, Owens DS et al. Genetic associations with valvular calcification and aortic stenosis. N. Engl. J. Med. 368, 503–512 (2013) . Thanassoulis et al. performed a genome-wide association study of 6924 patients to demonstrate an association between genetic variants in the gene encoding lipoprotein(a) (Lp(a)) and aortic valve calcification, as well as clinical aortic stenosis, a disease for which the only treatment is surgical or catheter-based valve replacement. Given the ethnic variability in Lp(a) expression, the authors confirmed the association between Lp(a) and aortic valve calcification in European, African–American and Hispanic–American cohorts. This finding reveals a potential candidate for targeted treatment of aortic stenosis, as well as providing an important insight into the potential role of Lp(a) in cholesterol transport and fibrinolysis in its pathogenesis.